Remark on the vectorlike nature of electromagnetism and electric charge quantization - Pires, C. A D S [UNESP] (American Physical Society (APS), 1999)
In this work we study the structure of electromagnetic interactions and electric charge quantization in gauge theories of electroweak interactions based on semisimple groups. We show that in the standard model of electroweak interactions the structure of electromagnetic interactions is strongly correlated to the quantization pattern of electric charges. We examine these two questions also in all possible chiral bilepton gauge models of electroweak interactions. In all, we can explain the vectorlike nature of electromagnetic interactions and electric charge quantization together demanding nonvanishing fermion masses and anomaly cancellations. ©1999 The American Physical Society.